FEATURES OF FINANCIAL CONTROL IN THE HEALTHCARE SYSTEM (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
The organizational - methodological aspects of financial control in the healthcare system were considered in the scientific research work. The types of financial control and their application are scientifically - practically based. The results of financial control in the healthcare system and their documentation were studied.